Building Quality Islamic Schools through Total Quality Management - Febriani, Susanda; Sesmiarni, Zulfani (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to evaluate the implementation of Total Quality Management (TQM) in an Islamic school in Bukittinggi to answer the challenges of modern education, such as the need for efficient quality management, learning innovation, and stakeholder involvement. Using a qualitative approach with a case study method, this research involved the principal, teachers, students and parents as research subjects. Data were collected through observation, in-depth interviews, and documentation analysis. The results showed that the implementation of TQM improved customer satisfaction through teacher training, strengthening communication with parents, using innovative learning media, and transparency in school management. However, the main challenges faced include resistance to change in organizational culture, limited human resources, and an unoptimal communication system. To overcome these challenges, the proposed solutions include continuous training, active involvement of stakeholders and implementation of an integrated feedback system. The findings show that TQM not only improves the quality of education in Islamic schools but also creates a culture of continuous improvement that supports holistic student development. This research makes a significant contribution to the development of quality management strategies in Islamic education institutions in Indonesia.